Gender difference in requesting abdominoplasty, after bariatric surgery: Based on five years of experience in two centers in Sulaimani Governorate, Kurdistan Region/Iraq. (August 2018) - Ahmed, Hiwa O.; Arif, Sarmad H.; Abdulhakim, Sabah Abid; Kakarash, Aram; Ali Omer, Mohammad Amin; Nuri, Aree Majid; Omer, Hallo H.; Jalal, Hardi Kareem; Omer, Shahen H.; Muhammad, Nashadin Aziz
Abstract: Background: The increasing incidence of morbid obesity suggests that the quantity of bariatric surgical procedures will continue to multiply each year, many patients who have experienced massive weight loss are left with the dissatisfying consequences of loose and redundant skin, resulting in contour irregularities, an aesthetic and functional problem, and profound dissatisfaction with appearance, residual body image dissatisfaction, There is a subsequent increase in the number of patients seeking additional corrective procedures including abdominoplasty which considered as one of the most popular body-contouring procedures. Correcting skin excess, could improve all the corollaries, including body, and functional problems and gives profound satisfaction with appearance, it has shown to improve both psychological and social aspects of the patients' lives. Objectives: Is there a gender difference in seeking body countering after bariatric surgery for weight loss? Patients and methods: A longitudinal observational study includes 209 obese patients with mean age of 31 ± 8.6 years; (31 ± 9, 31 ± 7 years for female and male patients respectively). Gender ratio M/F = 1.94/1, mean BMI 40 ± 9 kg/m2sin (n = 138 female) and 45±8m2s in (n = 71 male) patients, and Waist circumference 109 ± 7 cm in female and 118 ± 4 cm in males. Results: Some female (n = 10, 7.25%) patients were seeking abdominoplasty from the third month after the operations were they have lost (21 ± 2 kg) of their excess weight, fourteen patients (10.14%), at 6 months and 27 patients (19.56%) at 12 months, but most of male patients were requesting abdominoplasty (n = 7, 09.86%) at 12 months after the operations. Male patients have shifted their ideal from weight loss to abdominoplasty after losing (50–70) of their excess weight 12 months after the operations. The main motivation of requesting abdominoplasty in female and male patients was physical difficulty because of redundant skin, and a smaller number in both genders were motivated by a friend or by a doctor. Conclusion: The motivation for abdominoplasty in females is parallel to the amount of EWL or waist circumference. Female patients are looking for body countering three months after surgery, while male patients more often than not request body shaping following one year after surgery, the age groups are invert in genders; female patients asking for body contouring in younger age group while male patients in older age group. Highlights: The rational for abdominoplasty was better body image and early shifting of their ideals. Some female patients were seeking abdominoplasty from the third month after the operations. The most common problem in female patients with redundant skin was Cloth's fashion problems. The main motivation of seeking abdominoplasty in both genders was physical difficulty. The age for abdominoplasty was revers in genders, earlier in female, & later in male patients.